1970
DOI: 10.1136/bmj.4.5733.495-d
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction.

Abstract: Snt,-I wish to report an unusual, yet important, complication of hysterotomy. This I believe will be of general medical interest, especially for those who are involved with undertaking termination of pregnancy.A 33-year-old housewife was admitted to hospital for abdominal termination of pregnancy and sterilization. The indications were parity, proctocolitis, and acute anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In addition, there was a significant negative correlation between FT3 and CARS score. These findings were in agreement with the study of Khan, 18 who reported a high rate of hypothyroidism in children with autism. Nir et al 19 reported larger diurnal variation in TSH serum levels in comparison with controls explaining the possible thyroid dysfunction in ASD in relation to hypothalamic–pituitary axis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, there was a significant negative correlation between FT3 and CARS score. These findings were in agreement with the study of Khan, 18 who reported a high rate of hypothyroidism in children with autism. Nir et al 19 reported larger diurnal variation in TSH serum levels in comparison with controls explaining the possible thyroid dysfunction in ASD in relation to hypothalamic–pituitary axis.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of lower TSH values in autistic children suggests that they may have hypothyroidism. This is supported by the early literature (Sherwin et al 1958, Khan 1970). However, it has been reported that levels of triiodothyronine (T3), thyroxine and TSH in autism were within the normal range, and that T3 was not therapeutically effective (Abassi et al 1978, Campbell et al 19876).…”
Section: Discussionsupporting
confidence: 69%
“…Other studies examining thyroid hormones have been inconsistent. A letter to editor in 1970 indicated a high rate of hypothyroidism (73%) in 62 children with ASD using T3 uptake testing, although two other small studies could not confirm thyroid dysfunction in ASD, finding no difference in thyroid‐stimulating hormone (TSH), thyroxin (T4) or T3 between ASD and control children . Other studies suggest that ASD has been associated with a family history of autoimmune thyroid disorders and that deficiencies in thyroid function may be present before or at birth in children with ASD .…”
Section: Introductionmentioning
confidence: 99%